The impact of the 1952 London smog event and its relevance for current wood-smoke abatement strategies in Australia. (2nd September 2019) - Read, Catherine; Parton, Kevin A.
ABSTRACT: There is a certain complacency about air pollution in rural towns in Australia. An image of crystal clear skies seems to dominate general perceptions, and few locations actually monitor air pollution levels. Nevertheless, where measurements have been made, particulates have been shown to be the major type of air pollution, and they do reach levels expected to impact on human health. In this article, the contemporary attitudes and behaviour of the government and the population in rural and regional Australia are shown to have a strong resemblance to those that were prevalent prior to the smog events in London in December 1952. Wood smoke poses similar significant health issues in many countries. Insights obtained from the London events, together with more recent research results, are applied to the Australian situation to suggest policy options that are likely to be successful in overcoming the health effects of particulate pollution. Implications : The contemporary attitudes and behaviour of the government and the population in rural and regional Australia are shown to have a strong resemblance to those that were prevalent prior to the smog events in London in December 1952. Insights obtained from the London event of 1952, together with more recent research results, are applied to the Australian situation to suggest policy options that are likely to be successful in overcoming the health effects of particulate pollution.